Radical modulated regioselective difunctionalization of vinyl enynes: tunable access to naphthalen-1(2H)-ones and allenic alcohols. Issue 18 (14th February 2022) - Xie, Xiao-Yu; Xu, Yun-Fang; Li, Yang; Wang, Xiao-Dong; Zhu, Jie; Wu, Lei
Abstract : A novel and efficient radical-modulated difunctionalization of vinyl enynes has been disclosed using TEMPO as a radical regulator. Abstract : A novel and efficient radical-modulated difunctionalization of vinyl enynes has been disclosed using TEMPO as a radical regulator. Facile access to structurally diverse 3-bromo-naphthalen-1(2 H )-ones and 4-bromo-allenic alcohols was realized via 1, 2-addition/1, 2-migration or 1, 4-addition, respectively. This protocol represents the first example of radical-modulated metal-free difunctionalization of 1, 3-enynes with high regioselectivity.